CRIMINAL RESPONSIBILITY OF BUSINESS ACTORS FOR THE DISTRIBUTION OF FOOD CONTAINING DANGEROUS SUBSTANCES - Winarto Waryadi; Arista Candra Irawati (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2025)
ABSTRACTThe distribution of food containing hazardous chemicals remains a serious issue in consumer protection in Indonesia. Although the Consumer Protection Law, the Food Law, and various derivative regulations have provided a clear legal basis, practices in the field show that law enforcement is still weak. This study aims to analyze the criminal liability of business actors for the distribution of hazardous food by examining the applicable legal norms and their implementation in the field. The method used is empirical legal research with a normative juridical approach and field studies, through analysis of regulations, court decisions, and data from the Food and Drug Supervisory Agency (BPOM). The results of the study show that the forms of business operator liability can be civil, administrative, and criminal; however, obstacles such as limited resources, weak coordination between agencies, low legal awareness, and inconsistent court decisions mean that criminal sanctions are rarely applied to the fullest extent. This study emphasizes the importance of strengthening coordination among law enforcement agencies, harmonizing regulations, and applying consistent criminal sanctions to realize consumer protection. Theoretically, this study enriches the study of economic criminal law and consumer protection, while practically providing policy recommendations for improving the hazardous food control system in Indonesia.